EL ORIGEN DE LOS POSTCANINOS GONFODONTES DE ANDESCYNODON MENDOZENSIS BONAPARTE (CYNODONTIA, TRAVERSODONTIDAE) (Ameghiniana, 2013)
Postcanine gomphodont morphology of Andescynodon mendozensis Bonaparte (Traversodontidae) is compared with that of the primitive carnivorous cynodonts Cromptodon mamíferoides Bonaparte and Thrinaxodon liorhinus Seeley (Galesauridae). The dental structure of the Traversodontidae could have originated from a series of modifications starting from a morphological type already present in late Permian and early Triassic camivorous cynodonts (e. g., Galesauridae). These changes should have inc1uded: 1) a .relative shortening of the teeth; 2) expansion of their lingual surface; 3) appearance of a transverse crest; 4) a lateralization of the sectorial crest, and 5) the development of deep and broad functional dental basins. As a result, contact between teeth and food was greatly increased, in agreement with a novel action of puncturing, cutting and macerating it. This structural and biomechanical advance in cynodont dental morphology could account for the extraordinary diversity and expansion of the Traversodontidae during the Triassic.